História, verdade e linguagem: a historicidade das ciências. Entrevista com o Prof. Dr. Carlos Alvarez Maia - Silva, Emilly Joyce Oliveira Lopes; Araújo, George Fellipe Zeidan Vilela; Silva, Paloma Porto (Temporalidades, 2011)
Entrevista com o Prof. Dr. Carlos Alvarez Maia.